Analysis of pericentromere composition and structure elucidated the history of the Hieracium alpinum L. genome, revealing waves of transposable elements insertions - Alexander Belyayev; Begoña Quirós de la Peña; Simon Villanueva Corrales; Shook Ling Low; Barbora Frejová; Zuzana Sejfová; Jiřina Josefiová; Eliška Záveská; Yann J.K. Bertrand; Jindřich Chrtek; Patrik Mráz (Mobile DNA, 2024)
Abstract Background The centromere is one of the key regions of the eukaryotic chromosome. While maintaining its function, centromeric DNA may differ among closely related species. Here, we explored the composition and structure of the pericentromeres (a chromosomal region including a functional centromere) of Hieracium alpinum (Asteraceae), a member of one of the most diverse genera in the plant kingdom. Previously, we identified a pericentromere-specific tandem repeat that made it possible to distinguish reads within the Oxford Nanopore library attributed to the pericentromeres, separating them into a discrete subset and allowing comparison of the repeatome composition of this subset with the remaining genome. Results We found that the main satellite DNA (satDNA) monomer forms long arrays of linear and block types in the pericentromeric heterochromatin of H. alpinum, and very often, single reads contain forward and reverse arrays and mirror each other. Beside the major, two new minor satDNA families were discovered. In addition to satDNAs, high amounts of LTR retrotransposons (TEs) with dominant of Tekay lineage, were detected in the pericentromeres. We were able to reconstruct four main TEs of the Ty3-gypsy and Ty1-copia superfamilies and compare their relative positions with satDNAs. The latter showed that the conserved domains (CDs) of the TE proteins are located between the newly discovered satDNAs, which appear to be parts of ancient Tekay LTRs that we were able to reconstruct. The dominant satDNA monomer shows a certain similarity to the GAG CD of the Angela retrotransposon. Conclusions The species-specific pericentromeric arrays of the H. alpinum genome are heterogeneous, exhibiting both linear and block type structures. High amounts of forward and reverse arrays of the main satDNA monomer point to multiple microinversions that could be the main mechanism for rapid structural evolution stochastically creating the uniqueness of an individual pericentromeric structure. The traces of TEs insertion waves remain in pericentromeres for a long time, thus “keeping memories” of past genomic events. We counted at least four waves of TEs insertions. In pericentromeres, TEs particles can be transformed into satDNA, which constitutes a background pool of minor families that, under certain conditions, can replace the dominant one(s).